1996
DOI: 10.1046/j.1365-2443.1996.28028.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and conservation of the heat‐shock transcription factor σ32

Abstract: Heat shock and other stresses induce a set of genes encoding molecular chaperones and proteases through increase in the level of transcription factor 32 in Escherichia coli. Some of the cis-and transacting factors involved in the control of synthesis (translation), degradation and activity of 32 have been identified and characterized. These studies contribute to our understanding of early events of the heat-shock response, including modes of interaction between chaperones and 32 . Besides, analysis of 32 homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Moreover, the increased 32 level under these conditions results primarily from stabilization and not from increased synthesis of 32 (17,39). These and other data suggested that stabilization and enhanced synthesis of 32 that occur upon exposure to high temperature involve two distinct pathways or mechanisms (11,17,43).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, the increased 32 level under these conditions results primarily from stabilization and not from increased synthesis of 32 (17,39). These and other data suggested that stabilization and enhanced synthesis of 32 that occur upon exposure to high temperature involve two distinct pathways or mechanisms (11,17,43).…”
mentioning
confidence: 69%
“…Whereas induction of 32 synthesis occurs at the translation level mediated by the rpoH mRNA secondary structure (25,45), stabilization occurs presumably by sequestering 32 from DnaK and DnaJ chaperones (34,35) or proteases such as FtsH/HflB (13,37). This homeostatic response appears to be regulated by a complex feedback circuit involving chaperones, proteases, and other components of signalling pathways that have yet to be identified (2,6,11,43,44).…”
mentioning
confidence: 99%
“…characterized as a component of the heat-shock response in Escherichia coli (reviewed by Bukau, 1993 ;Georgopoulos et al, 1994 ;Yura, 1996). In response to a sudden increase in temperature or other stresses, the levels of σ$# rise transiently because of increased synthesis and protein stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the rpoH-lacZ gene fusion suggested involvement of an internal region of 32 (region C; 122-144 aa) in the control of both DnaK-DnaJ-mediated shutoff of synthesis and stability of the 32 -␤-galactosidase fusion protein (24), although core RNA polymerase binding rather than DnaK binding or 32 stability was recently shown to be affected by mutations in this region (25,26). In any event, shutoff of 32 synthesis could not be separated from the control of 32 stability, despite the clear distinction between controls of heat-induced synthesis and stability of 32 (3,4,27). In addition, the changing stability of 32 at different phases prevented accurate determination of synthesis rates during the heat-shock response.…”
mentioning
confidence: 99%